Peran Remaja Masjid Terhadap Pengelolaan Ekowisata Permandian Air Panas Samaen Maros - Mutmainnah (Jurnal Berita Sosial, 2022)
The role of mosque youth through the management of hot spring ecotourism. The type of research used is descriptive qualitative research, using a sociological approach. The data sources of this research are primary data sources and secondary data sources, then the data collection methods used are observation, interviews, and documentation methods. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of the study show that: first, the role of mosque youth in improving the community’s economy through ecotourism management of the Samaenre hot springs, Kec. Mallawa Kab. Maros is the management of hot spring ecotourism in maintaining tickets, maintaining the cleanliness of the hot spring pool, being a tourist guide, helping market oyster mushrooms. Second, the obstacles faced by mosque youth in managing ecotourism in hot springs are the lack of knowledge about ecotourism management, mosque youth have not seen the otential of ecotourism as their main livelihood, lack of mosque youth time, weather factors and natural conditions, and the lack of community participation.